Validitas Komik Fisika Digital Untuk Melatihkan Berpikir Kritis Peserta Didik Pada Materi Gaya Gesek - Savitri, Irma; Kholiq, Abd (Universitas Negeri Surabaya, 2023)
Abstract 21st century education, implementing learning by utilizing the development of science and technology. 21st century learning is not just knowledge that is relied on, but also involves skills in learning. One of the skills in the 21st century is critical thinking skills. Critical thinking is an ability that students must have to interpret, analyze, explain, conclude, and evaluate, in problem solving activities. The development of 21st century skills must be carried out by educators in order to achieve effective and efficient learning objectives. In developing 21st century skills, educators can use instructional media by utilizing technological developments in the 21st century. Thus, the research aims to produce digital physics comics to train students' critical thinking on frictional material which is declared valid. This development research uses the DDD-E model with the stages of decide, design, develop, and evaluate. The validity of digital physics comics was obtained based on instrument validation by the validator on media, material, and language aspects. The validators consisted of 3 expert lecturers majoring in physics at Surabaya State University. The results showed that the percentage of validity on the media aspect was 90%, on the material aspect was 93%, and on the language aspect was 95%. Based on these results, the validity of the comic was obtained by an average validation score percentage of 93% with a very valid category. Thus digital physics comics are declared feasible to be used as physics learning media to train students' critical thinking on friction material,. Keywords: digital physics comics, critical thinking, frictional force